2017
DOI: 10.14254/2071-789x.2017/10-4/8
|View full text |Cite
|
Sign up to set email alerts
|

The Structure – Conduct – Performance Paradigm in the European Union Banking

Abstract: ABSTRACT. In this study we investigate the structure and performance at the European Union (EU) banking market as a whole between 2008 and 2015. The structure of this banking market was measured by two main concentration indices: the Herfindahl-Hirschman Index (HHI) and the Concentration Ratio for 5 largest banks (CR5). The results show a stable development in concentration until 2012, and a significant decrease in 2012. Since 2013, the level of concentration increased, reaching its historical maximum at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Findings from the study suggested that market structure and conduct significantly determined the performance of commercial banks in Ghana within the study period. This is congruent with a similar study conducted by Gavurova, Kocisova and Kotaskova (2017), which examined the structure and performance of European Union (EU) banking markets using the SCP paradigm. The main problem or gap observed from these studies is the dearth of studies in African real estate markets that look at the performance of REITs from the perspective of the conduct, structure and performance of REIT companies.…”
Section: Literature Reviewsupporting
confidence: 87%
“…Findings from the study suggested that market structure and conduct significantly determined the performance of commercial banks in Ghana within the study period. This is congruent with a similar study conducted by Gavurova, Kocisova and Kotaskova (2017), which examined the structure and performance of European Union (EU) banking markets using the SCP paradigm. The main problem or gap observed from these studies is the dearth of studies in African real estate markets that look at the performance of REITs from the perspective of the conduct, structure and performance of REIT companies.…”
Section: Literature Reviewsupporting
confidence: 87%
“…Source: Taken from Madura (2017) Gavurova et al (2017) investigated the structure and performance in the European Union (EU) banking market during 2008-2015. The banking market structure was measured by two main concentration indicators, which are Herfindahl-Hirschman Index (HHI) and the Concentration Ratio for 5 largest banks (CR5).…”
Section: Figure-1 Conceptual Frameworkmentioning
confidence: 99%
“…Hicks (1935, p. 8) "quiet life" hypothesis (QLH), which posits that as banks amass market power when industry concentration increases, managers can raise price and would exhibit no motivations to curtail costs (Lelissa & Kuhil, 2017;Berger & Hannan, 1998). The finding that QLH holds in the industry is consistent with Gavurova, Kocisova, and Kotaskova (2017) view of EU banking, Repkova and Stavarek (2013) outlook of the Czech banking industry, and Berger and Hannan (1998) assessment of the US banking industry. However, it contradicts Mensi & Zouari (2010) and Casu and Giradone (2009) findings that show no support for QLH.…”
Section: Resultsmentioning
confidence: 81%